TRPV4 enhances cellular uptake of aminoglycoside antibiotics - Karasawa, Takatoshi (2008)
The cochlea and kidney are susceptible to aminoglycoside-induced toxicity. The non-selective cation channel TRPV4 is expressed in kidney distal tubule cells, and hair cells and the stria vascularis in the inner ear. To determine if TRPV4 is involved in aminoglycoside trafficking, we developed a murine proximal tubule cell line KPT2 and a distal tubule cell line KDT3. TRPV4 expression was confirmed in KDT3 cells but not in KPT2 cells. Removal of extracellular Ca(2+) significantly enhanced gentamicin-Texas Red (GTTR) uptake by KDT3, indicative of drug uptake by non-selective cation channel permeation. To determine if TRPV4 is permeable to GTTR, stable cell lines were generated that express TRPV4 in KPT2 (KPT2-TRPV4). KPT2-TRPV4 cells took up more GTTR than control cell lines (KPT2-pBabe) in the absence of extracellular Ca(2+). TRPV4-dependent GTTR uptake was abolished by a point mutation within the critical channel pore region, suggesting that GTTR permeates the TRPV4 channel. In an endolymph-like extracellular environment, clearance of GTTR was attenuated from KPT2-TRPV4 cells in a TRPV4-dependent fashion. We propose that TRPV4 may play a role in aminoglycoside uptake and retention in the cochlea.